Resilience of global supply chain: Facts and implications - Alicia García Herrero (Asian Development Bank Institute (ADBI), 2023)
Global supply chains have been growing, but also evolving, for decades. The People's Republic of China (PRC) has been acquiring an increasingly central role in global value chains, but things might be starting to change. The trade war between the United States (US) and the PRC and, especially, the COVID-19 pandemic, followed by Russia's invasion of Ukraine, have been crucial shocks to the good functioning of supply chains. Companies, as well as governments, are focusing more on resilience than on efficiency, which is already bringing about some reshuffling of supply chains, according to available surveys. This paper reviews the PRC's central role in the global value chain and the consequences of this, as well as the bottlenecks created by the COVID-19 pandemic and the Russian invasion of Ukraine. Government action, including legislation, has been introduced in several countries, such as Japan, the Republic of Korea, the European Union, and the US, to increase the resilience of global value chains. That said, many of the decisions made by companies to reshuffle production away from the PRC may be incentivized by the strong need for diversification amidst the growing geopolitical turbulence and the PRC's worsening medium-term economic prospects. In other words, companies diversifying their production away from the PRC-as shown in the recent slow-down in mergers and acquisitions into the PRC and the simultaneous increase in India and Association of Southeast Asian Nations countries-might be the result of a rather rational decision based on an economic rationale and, in some cases, also on government action.
Keywords: F15; F51; F52; 330; global supply chain; supply chain resilience; international trade